2021
DOI: 10.1177/00048674211058684
|View full text |Cite
|
Sign up to set email alerts
|

Plasma neurofilament light chain protein is not increased in treatment-resistant schizophrenia and first-degree relatives

Abstract: Objective: Schizophrenia, a complex psychiatric disorder, is often associated with cognitive, neurological and neuroimaging abnormalities. The processes underlying these abnormalities, and whether a subset of people with schizophrenia have a neuroprogressive or neurodegenerative component to schizophrenia, remain largely unknown. Examining fluid biomarkers of diverse types of neuronal damage could increase our understanding of these processes, as well as potentially provide clinically useful biomarkers, for ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 59 publications
(97 reference statements)
0
17
0
Order By: Relevance
“…Participants were from the Cooperative Research Centre (CRC) Psychosis Study, a cross-sectional study that recruited people aged 18-65 years from inpatient and outpatient services in Melbourne, Australia, between 2012-2017 (n=82), who were on clozapine and had a diagnosis of treatment- resistant schizophrenia (TRS), defined as failure to respond to adequate trials of two or more antipsychotics, as previously described (Bousman et al, 2019; Eratne et al, 2021; Mostaid et al, 2017) The TRS biobank is detailed here: https://researchdata.ands.org.au/treatment-resistant-schizophrenia-biobank/1325206…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Participants were from the Cooperative Research Centre (CRC) Psychosis Study, a cross-sectional study that recruited people aged 18-65 years from inpatient and outpatient services in Melbourne, Australia, between 2012-2017 (n=82), who were on clozapine and had a diagnosis of treatment- resistant schizophrenia (TRS), defined as failure to respond to adequate trials of two or more antipsychotics, as previously described (Bousman et al, 2019; Eratne et al, 2021; Mostaid et al, 2017) The TRS biobank is detailed here: https://researchdata.ands.org.au/treatment-resistant-schizophrenia-biobank/1325206…”
Section: Methodsmentioning
confidence: 99%
“…Samples and data were pooled from healthy people (n=96) with no current or past psychiatric or neurological illness, from the CRC Psychosis Study (healthy controls age-matched to TRS, and healthy parents and siblings of participants with TRS), as described previously (Eratne et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Neurofilament light (NfL) is one of three subunits of a neuroaxonal cytoskeletal protein common to myelinated axons, with elevated levels in cerebrospinal fluid (CSF) and blood associated with neuronal injury and a marker of diagnosis, staging and prognosis, in a diverse range of neurological and neurodegenerative disorders [25][26][27][28][29][30][31]. Numerous studies have demonstrated elevated CSF and blood NfL in bvFTD compared to controls, as well as primary psychiatric disorders [29][30][31][32][33][34][35][36][37][38]. Recent expert consensus guidelines and recommendations have recommended NfL as a biomarker to assist with differentiating bvFTD from primary psychiatric disorders [11].…”
Section: Introductionmentioning
confidence: 99%